2017
DOI: 10.1016/j.clinthera.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin 8% Patch Versus Oral Neuropathic Pain Medications for the Treatment of Painful Diabetic Peripheral Neuropathy: A Systematic Literature Review and Network Meta-analysis

Abstract: This NMA suggests that the efficacy observed with the capsaicin 8% patch is similar to that observed with oral agents (ie, pregabalin, duloxetine, gabapentin) in patients with PDPN. The oral agents were associated with a significantly elevated risk of somnolence, dizziness, fatigue, and discontinuation because of AEs compared with placebo. The capsaicin 8% patch was as effective as oral centrally acting agents in these patients with PDPN but offers systemic tolerability benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 55 publications
0
55
0
9
Order By: Relevance
“…Patches with capsaicin 8% have also been studied in painful DSPN, with conflicting results [66]. Nonetheless, some evidence points to superiority in comparison with oral pregabalin, duloxetine, and gabapentin for pain relief among DSPN patients [67]. Although not formally approved [68], a single application of this patch may provide up to 12 weeks of pain relief [69].…”
Section: Topical Treatmentmentioning
confidence: 99%
“…Patches with capsaicin 8% have also been studied in painful DSPN, with conflicting results [66]. Nonetheless, some evidence points to superiority in comparison with oral pregabalin, duloxetine, and gabapentin for pain relief among DSPN patients [67]. Although not formally approved [68], a single application of this patch may provide up to 12 weeks of pain relief [69].…”
Section: Topical Treatmentmentioning
confidence: 99%
“…Safe treatment is possible in specialist pain clinics, whose staff includes doctors and nurses trained in this area. Capsaicin administered at this concentration can cause blindness in contact with the cornea of the eye [41].…”
Section: Treatment Of Neuropathic Painmentioning
confidence: 98%
“…Bezpieczne leczenie jest możliwe w specjalistycznych poradniach leczenia bólu, w których pracują przeszkoleni w tym zakresie lekarze i pielęgniarki. Kapsaicyna podana w tym stężeniu, przy kontakcie z rogówką oka, może spowodować ślepotę [41].…”
Section: Leczenie Bólu Neuropatycznegounclassified
“…Similar to fibromyalgia, tricyclic antidepressants and opioids are commonly used to treat the symptoms of diabetic peripheral neuropathy (Javed et al, 2015;Tajti et al, 2016) and a capsaicin patch has been shown to display similar efficacy to oral drugs, albeit with limits in tolerability (van Nooten et al, 2017). Both gabapentin and pregabalin are also effective treatments, with pregabalin recommended at a dose of 300 mg to 600 mg daily resulting in a significant reduction in pain scores (Juhn et al, 2015).…”
Section: Pregabalin In Diabetic Peripheral Neuropathymentioning
confidence: 99%